2017
DOI: 10.1080/15384101.2017.1282585
|View full text |Cite
|
Sign up to set email alerts
|

The role of WRNIP1 in genome maintenance

Abstract: WRNIP1 interacts with WRN helicase, which is defective in the premature aging disease Werner syndrome. WRNIP1 belongs to the AAA+ ATPase family and is conserved from Escherichia coli to human. The protein contains an ubiquitin-binding zinc finger (UBZ) domain at the N terminus and an ATPase domain in the middle region. In addition to WRN, WRNIP1 interacts with proteins involved in multiple cellular pathways, including RAD18, monoubiquitylated PCNA, DNA polymerase δ, RAD51, and ATMIN. Mgs1, the yeast homolog of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 42 publications
0
36
0
1
Order By: Relevance
“…Previous results have found that the Mgs1/WRNIP1/RarA protein is associated with the replication fork and involved in replication restart. It was proposed that Mgs1/WRNIP1 might stimulate detachment of the replicative Polδ from ubiquitylated PCNA, and facilitate the recruitment of the translesion synthesis polymerase Polη to sites of DNA damage ( 1 ). Similarly, model 2 for RarA Eco action (see Introduction) proposed that this protein facilitates the replacement of Pol III Eco by a bypass DNA polymerase ( 5 , 15 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous results have found that the Mgs1/WRNIP1/RarA protein is associated with the replication fork and involved in replication restart. It was proposed that Mgs1/WRNIP1 might stimulate detachment of the replicative Polδ from ubiquitylated PCNA, and facilitate the recruitment of the translesion synthesis polymerase Polη to sites of DNA damage ( 1 ). Similarly, model 2 for RarA Eco action (see Introduction) proposed that this protein facilitates the replacement of Pol III Eco by a bypass DNA polymerase ( 5 , 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…The bacterial r eplication a ssociated r ecombination protein A, RarA, belongs to a highly-conserved family of AAA + ATPases, where also the yeast Mgs1 ( M aintenance of genome s tability 1 ) and mammal WRNIP1 (Werner [ WRN ] I nteracting P rotein 1 ) proteins are included ( 1 ). The Mgs1/WRNIP1/RarA enzymes play a crucial, although poorly characterised role in replication restart ( 2–6 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…44 Mgs1, as well as its human homolog, plays a crucial role in genome maintenance. 42,44 Cells lacking Mgs1 show an elevated rate of mitotic recombination and Mgs1 overexpression sensitizes cells to DNA damaging agents, such as MMS, HU, and UV-light. 42,45,46 Despite the various published phenotypes related to nonphysiological levels of Mgs1 45,46 the exact function of Mgs1 is not clear.…”
Section: Introductionmentioning
confidence: 99%
“…Although the function of Mgs1 is unclear, this protein has been linked to DDT due to the interaction with PCNA described above and because Mgs1 becomes essential in the absence of Rad6/ Rad18 (22,23). In addition, consistent with the requirement of Mgs1 and its homologs for genome stability during chromosome replication, it was recently shown that human WRNIP1, with proposed roles in DNA transactions (24), is important for the maintenance of the integrity of stalled forks and for replication resumption (25). Likewise, it has been proposed that Bacillus subtilis RarA assembles at blocked forks and plays a role in preventing pathological replication fork restart (26).…”
Section: Introductionmentioning
confidence: 83%